Optically-driven switching of a planar nematic liquid crystal cell with parallel rubbing - Nersesyan, Varsenik (Photonics Letters of Poland, 2017)
This letter reports on the switching of a planar nematic liquid crystal cell with parallel rubbing of the alignment layers, under the application of a voltage, when there is initially an optical field. The voltage application over the liquid crystal in such a cell leads normally to the formation of multiple domains because there is the two switching directions are equivalent. However, an incident optical field under an angle will locally reorient the director and break the symmetry between the equivalent switching directions. The subsequent application of a voltage pulse amplifies the tilt angle and leads to the formation of a dominant domain, with an order of magnitude larger size than the optical beam profile. Several switching conditions are demonstrated for different incident angles of the beam. It is shown that the final switching direction of the entire cell is determined by the tilt angle of the optical field. The lensing effects due to the modified director distribution in the domain walls is analyzed qualitatively. Full Text: PDF References I. C. Khoo, Liquid crystals (2nd ed. Hoboken (NJ), Wiley, 2007) CrossRef A. Zolotko, V. Kitaeva, N. Kroo et al. OCBP. JETP Lett. 32, 158?162 (1980). DirectLink J. Beeckman, K. Neyts, X. Hutsebaut X, et al. "Simulations and experiments on self-focusing conditions in nematic liquid-crystal planar cells", Opt Express, 12, 1011? 1018 (2004). CrossRef M. Peccianti, C. Conti, G. Assanto, et al. "Electrically assisted self-confinement and waveguiding in planar nematic liquid crystal cells", Appl. Phys. Lett. 77, 7 ? 9 (2000). CrossRef N. Kravets, A. Piccardi, A. Alberucci et al, "Bistability with Optical Beams Propagating in a Reorientational Medium", Phys. Rev. Lett. 113, 023901 (2014) CrossRef A. Piccardi, N. Kravets, A. Alberucci et al, "Voltage-driven beam bistability in a reorientational uniaxial dielectric", APL Photonics 1, 011302 (2016). CrossRef V. Nersesyan, T. Brans, F. Beunis, R. Drampyan , J. Beeckman, K. Neyts, "Light-controlled reorientation of nematic liquid crystal driven by an electric field", Liquid crystals, 43, 1422-1430 (2016). CrossRef J. Beeckman, K. Neyts, W. Cort, et al. "Non-linear light propagation and bistability in nematic liquid crystals", Proc SPIE 7414, 74140K (2009). CrossRef